Which Winegrape Varieties are Grown Where? a global empirical picture - Anderson, Kym (University of Adelaide Press, 2013)
This new database charts exactly what varieties are grown in which regions around the world. Since the data sets are based on two broad census periods, in 2000 and 2010, readers can also follow major planting trends around the world during the first decade of this new century.